2022
DOI: 10.3390/ma15031000
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Abrasive and Acidic Aggressions on the Surface Condition of Flowable Composite Resin

Abstract: The aim of this in vitro study was to evaluate the effect of hydrochloric acid associated with the abrasive effect of toothbrushing on the surface condition of three flowable composite resins used for direct restoration. Seventy samples of each composite resin: Grandio Flow (VOCO, Germany)—group A, Filtek Ultimate Flow (3M-ESPE, MN, USA)—group B, G-aenial Flo X (GC Europe)—group C were prepared, submersed in hydrochloric acid 30% for 60 min and then submitted to simulated toothbrushing procedure using 5000 cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…At the same time, the obtained results in our study showed that for the cavities restored with inlay technique, no significant differences in marginal adaptation were observed between the cervical margin and the cervical margin relocated with flow composite resin, these results being in agreement with the conclusions of some studies [28][29][30] that found no differences between the marginal sealing at the cervical margins. Fronza et al [31] reported that the use of flow composite resins did not prevent the appearance of marginal microleakage gaps at the cervical margin.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, the obtained results in our study showed that for the cavities restored with inlay technique, no significant differences in marginal adaptation were observed between the cervical margin and the cervical margin relocated with flow composite resin, these results being in agreement with the conclusions of some studies [28][29][30] that found no differences between the marginal sealing at the cervical margins. Fronza et al [31] reported that the use of flow composite resins did not prevent the appearance of marginal microleakage gaps at the cervical margin.…”
Section: Discussionsupporting
confidence: 92%
“…The Vickers hardness of the experimental composite resin was not affected by submersion in NaOH solution for 7 days. Other studies have reported significant changes in physical and mechanical properties after this aging procedure [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citric acid is able to chelate ionic components present in glass ionomer-based dental biomaterials and to determine a marked extent of GICs dissolution [ 25 ]. Phosphoric acid also can chelate ions to form water-soluble complexes [ 26 ]. Exposure to acidic environment could have a detrimental effect on glass ionomer biomaterials.…”
Section: Discussionmentioning
confidence: 99%